Infectious Bovine Rhinotracheitis Virus of Cattle and Buffaloes - Saw, Plei Saw (1983)
Infectious bovine rhinotracheitis virus infection in cattle has been reported throughout the world. The study of infectious bovine rhinotracheitis in buffalo was very limited. There was no report on infectious bovine rhinotracheitis in cattle and buffalo in Malaysia. A serological study on the prevalence of infectious bovine rhinotracheitis in cattle and buffalo in 10 states of Peninsular Malaysia showed that 52.52 per cent of the cattle and 65.07 per cent of the buffaloes had neutralizing antibodies to infectious bovine rhinotracheitis virus. Neutralizing antibodies were detected in 532 out of the 1013 serum samples from cattle and in 298 out of the 458 serum samples from buffaloes. The titre of the serum neutralizing antibodies ranged from 1:4 to 1:256. Four cattle and four buffaloes with neutralizing antibodies to infectious bovine rhinotracheitis virus were treated with dexamethazone at 0.1mg. per kilogram of body weight for 7 consecutive days. Treatment of these animals with dexamethazone resulted in shedding of virus. Viruses were isolated from nasal cavities and vaginas of the cattle and buffaloes in bovine embryonic kidney cells. The isolates were identified as infectious bovine rhinotracheitis virus by virus neutralizationtest. The viruses isolated from nasal cavity and vaginal mucosa of buffaloes were designated UPM BB 1 and UPM BB 2 respectively while the viruses isolated from nasal cavity and vaginal mucos a of cattle were designated UPM Be 1 and UPM Be 2 respectively. The 4 virus isolates had infective titres ranging from 10^6.8 to 10^7.8 Pfu per mL. The four infectious bovine rhinotracheitis virus isolates were then subjected to 3 cycles of plaque purification. The cloned infectious bovine rhino tracheitis viruses were further purified by rate zonal ultracentrifugat ion in 10 to 40 percent potassium tartrate. Examination of purified viruses under the electron microscope revealed virus morphology similar to that of herpes virus. The four purified virus preparations were also identified as infectious bovine rhinotracheitis virus by immune electron microscopy.